The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1128/aac.43.6.1497
|View full text |Cite
|
Sign up to set email alerts
|

Rifampin and Rifabutin Resistance Mechanism in Helicobacter pylori

Abstract: Eighty-one clinical isolates of Helicobacter pylorishowed no resistance to rifampin (MIC range, 0.032 to 2 μg/ml; MIC at which 50% of isolates are inhibited [MIC50], 0.25 μg/ml). The MIC50 of rifabutin was 0.008 μg/ml (n = 16). All resistant laboratory mutants of H. pylori ATCC 43504 showed amino acid exchanges in codons 524 to 545 or codon 585 of the rpoB gene, corresponding to the gene sequences from Mycobacterium tuberculosis andEscherichia coli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
126
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(132 citation statements)
references
References 12 publications
4
126
1
1
Order By: Relevance
“…There is a low prevalence of H. pylori resistance to rifampicin and rifabutin. Heep et al found no resistance to rifampicin in 81 clinical isolates of H. pylori in Germany (19). Similarly, Fujimura et al from Japan detected no rifampicin resistance among 52 H. pylori isolates.…”
Section: Discussionmentioning
confidence: 95%
“…There is a low prevalence of H. pylori resistance to rifampicin and rifabutin. Heep et al found no resistance to rifampicin in 81 clinical isolates of H. pylori in Germany (19). Similarly, Fujimura et al from Japan detected no rifampicin resistance among 52 H. pylori isolates.…”
Section: Discussionmentioning
confidence: 95%
“…12,14 Thus, the rate of H. pylori infection in patients with NTM who have been treated with a combination of clarithromycin and rifampicin is of great interest. In the present study, the rate of H. pylori infection in patients with NTM who had been administered antimicrobial agents, including clarithromycin, longterm, was found to be significantly lower (33.3%; P = 0.0006) than the general prevalence of H. pylori infection in Japanese adults over 40 years old who had had routine upper gastrointestinal endoscopy and no H. pylori eradication (77.5%; 145 of 187 patients).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, selection of resistant H. pylori strains has been low in experimental conditions. Thus, until now, no rifabutin-resistant strain has been isolated from patients who were or were not treated for H. pylori infection [31]. • Perri et al [33,34] used a 1-week regimen of pantoprazole, amoxicillin, and rifabutin in patients who were still infected with H. pylori after two or more courses of 1-week triple therapies, with an eradication rate of 71% by intention-to-treat analysis.…”
Section: Rifabutin-based Rescue Regimensmentioning
confidence: 97%
“…In this respect, rifabutin-based rescue therapies represent an encouraging strategy for eradication failures. H. pylori has been proved to be highly susceptible in vitro to rifabutin, a rifamycin derivative of the established tuberculostatic drug [30][31][32]. Furthermore, selection of resistant H. pylori strains has been low in experimental conditions.…”
Section: Rifabutin-based Rescue Regimensmentioning
confidence: 99%